2018
DOI: 10.1002/clc.22969
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing reveals microsatellite DNA markers for response to dofetilide initiation in patients with persistent atrial fibrillation: A pilot study

Abstract: Background Dofetilide is a class III antiarrhythmic drug effective for the treatment of atrial fibrillation (AF). Dofetilide initiation (DI) associates with corrected QT interval (QTc) prolongation. Significant QTc prolongation during DI mandates dose adjustment or discontinuation of the drug. Microsatellite DNA are novel genetic markers associated with congenital and acquired health conditions. Hypothesis. DNA microsatellite polymorphism may associate with QTc response to dofetilide initiation in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Different studies have suggested both MYOZ1 ( 17 , 18 ) and SYNPO2L ( 19 , 20 ) both located on chromosome 10q22, as the likely causal genes driving the association. Studies suggesting MYOZ1 as the causal gene, have done so primarily based on eQTL studies showing an altered expression of the MYOZ1 gene in carriers of AF risk alleles identified through GWAS studies.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have suggested both MYOZ1 ( 17 , 18 ) and SYNPO2L ( 19 , 20 ) both located on chromosome 10q22, as the likely causal genes driving the association. Studies suggesting MYOZ1 as the causal gene, have done so primarily based on eQTL studies showing an altered expression of the MYOZ1 gene in carriers of AF risk alleles identified through GWAS studies.…”
Section: Discussionmentioning
confidence: 99%